2003
DOI: 10.1111/j.0013-9580.2004.24003.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Strategies for a Scottish National Epilepsy Guideline in Primary Care: Results of the Tayside Implementation of Guidelines in Epilepsy Randomized (TIGER) Trial

Abstract: Summary:  Purpose: To determine the effectiveness of two dissemination and implementation strategies to implement a national guideline for epilepsy management in primary care settings. Methods: Three‐arm cluster‐randomized controlled trial. The participants were general practitioners from 68 practices in Tayside, Scotland, and 1,133 of their patients with self‐reported epilepsy treated with antiepileptic medications (AEDs). Practices were randomized blind to a control, intermediate, or intensive intervention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 26 publications
2
38
0
1
Order By: Relevance
“…Although CPGs have been found in a variety of clinical settings, to improve the quality of care in a variety of clinical settings, 23 improvements can occur only if CPGs are implemented in clinical practice. Practical implementation of CPGs remains a challenge, especially in epilepsy, 14,15,17 and lack of applicability of CPGs has been cited as a reason for limited adoption of CPGs in clinical practice. 24 Other cited reasons for not Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although CPGs have been found in a variety of clinical settings, to improve the quality of care in a variety of clinical settings, 23 improvements can occur only if CPGs are implemented in clinical practice. Practical implementation of CPGs remains a challenge, especially in epilepsy, 14,15,17 and lack of applicability of CPGs has been cited as a reason for limited adoption of CPGs in clinical practice. 24 Other cited reasons for not Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…12 For example, a cardiac care study found that when CPG recommendations were followed, patients had lower rates of heart failure, recurrence of atrial fibrillation, and hospitalizations. 13 Unfortunately, this has not necessarily been the experience in epilepsy, 14,15 most likely because of the poor adoption of CPG recommendations into routine clinical practice. [14][15][16][17] Although CPGs can be useful for health professionals and have widespread application beyond the clinical setting, they are not without limitations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14,20,29 Clinical decision support tools, such as the one examined in this study, are a potential means of closing this gap and improving quality of care delivered. [30][31][32][33][34] They tend to Figure Examples of the tool before and after knowledge translation activities conducted throughout this study…”
Section: Discussionmentioning
confidence: 99%
“…Do they improve the lives of patients? To investigate this, Julian Davis and his colleagues (13) attempted to assess the impact of SIGN guideline number 21 on outcomes in primary care.…”
mentioning
confidence: 99%